Analiza Modlitwy Eucharystycznej G Kościoła Anglii - Bosak, Dominik (Warszawskie Studia Teologiczne, 2022)
The article is dedicated to the analysis of one of the contemporary eucharistic prayers of the Church of England. The author analyzes Eucharistic Prayer G, which is one of the main eucharistic prayers in the Church of England. Prayer G is included in the main volume of the liturgical series of Common Worship in Order One, which means that the Prayer is intended for widespread use in the liturgy of the Church of England. Prayer G apart from standard parts of every anaphora, such as the introductory dialogue or the institution narrative, contains also its own characteristics in its content. In the course of the analysis, the author points out specific features of the Prayer, which indicate uniqueness of Prayer G among other eucharistic prayers of the Church of England.